Catching the common cause: extraction and annotation of causal relations and their participants - Rehbein, Ines; Ruppenhofer, Josef (11th Linguistic Annotation Workshop - proceedings of the workshop, 2017)
Ines Rehbein, Josef Ruppenhofer. Proceedings of the 11th Linguistic Annotation Workshop. 2017.